Implementasi Media Flascard dalam Meningkatkan Kemampuan Membaca Anak Down Syndrome di SLB Negeri Purwosari - Pramista, Anisa Zahro Salsabila; Su’adah, Muthorida; Ruby, Arcivid Chorynia (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to understand the implementation of flashcard media in improving reading skills of children with Down syndrome at SLB Negeri Purwosari. The research was conducted using a descriptive qualitative approach through the stages of initial observation, planning, intervention implementation, and evaluation. The subject of this study is a second-grade student at SLB Negeri Purwosari who is 8 years old and has difficulties in reading basic words. Data collection techniques include observation, interviews, and documentation. Data analysis was conducted qualitatively through the stages of data reduction, data presentation, and conclusion drawing. The results of the study showed a significant increase in students' reading ability after being given learning using flashcard media for 10 meetings. The average reading ability score increased from 35 to 73.4, covering aspects of recognizing letters, spelling words, and reading simple sentences. The conclusion of this study is that the use of flashcard media is effective in helping to improve the reading ability of children with down syndrome through a visual approach that is concrete, interesting, and in accordance with the characteristics of the special needs of students